Dietary intakes and nutritional issues in inborn errors of immunity: a systematic review - Freer, Macey; Bhatia, Rani; Preece, Kahn; Pursey, Kirrilly M. (Frontiers in Immunology, 2024)
Introduction: Inborn errors of immunity (IEI) are characterized by an inherited dysregulation or absence of immune system components that can manifest clinically in complications that predispose an individual to feeding difficulties or impaired swallowing, digestion, and absorption. Treatment side-effects or altered requirements may further impair nutritional status. While adequate nutrition is necessary for optimal growth and immune function, little is known about nutritional intakes in IEI, and best practice nutrition guidelines are limited. This review aimed to synthesize current evidence on the dietary intakes, anthropometry and nutritional biochemistry in individuals with an IEI.A systematic review of literature published from database inception to March 2023 was conducted in accordance with the PRISMA guidelines. Articles eligible for inclusion reported anthropometric, biochemical, or dietary intake-related measures in pediatric or adult patients with a diagnosed IEI. Identified articles were screened for eligibility; data was synthesized descriptively.Results: A total of 4488 studies were retrieved of which 34 were included. Across studies, 2894 IEI individuals were included (age range 4 weeks to 83y), predominantly focusing on ataxia telangiectasia (AT) and common variable immunodeficiency (CVID). A significant association between inadequate energy intakes and IEI was identified (n=6 studies); however, there was significant variability in adequacy of macro-and micronutrients across studies. Patients with IEI were at risk of malnutrition (range 30% to 70%); although anthropometric assessment measures were not consistent across studies. Biochemical assessments found patients were also at risk of micronutrient deficiencies including vitamin D.Discussion: This review identified few studies assessing dietary intakes, anthropometry and nutritional biochemistry in patients with IEI, with considerable heterogeneity across studies. Future longitudinal studies using consistent validated dietary assessment tools and anthropometric measures in diverse IEI patient populations are needed. This review reinforces the need for dietetic input in people with an IEI and the development evidence-based clinical practice guidelines for people with an IEI.